A corneal endothelium cell analyzer for slit lamps. - Ventura, L.
An optical system that attaches to a slit lamp is an alternative to the cost and limitations of specular microscopes. In order to overcome the limitations of subjective assessment of all the endothelial layers, the difficulties of manipulation, high cost, and analysis of several parts of the cornea, we have developed a system that can be attached to the slit lamp (290× nominal magnification of the image of the cells displayed on a PC monitor and a dedicated software for image treating and cells counting). Results are in good agreement with measurements done in specular microscopes (correlation coefficient is 0.98081) and the automatic counting method is also in good agreement with the interactive counting method (correlation coefficient is 0.95798).
Keywords: PC monitor; Automatic counting method; Corneal endothelium cell analyzer; Correlation coefficient; Dedicated software; Donated corneas evaluation; Effective optical method; Interactive counting method; Manipulation difficulties; Nominal magnification; Optical system; Slit lamps; Specular microscopes; Subjective assessment limitations